Enhanced Faraday rotation by crystals of core-shell magnetoplasmonic nanoparticles - P. Varytis; P.A. Pantazopoulos; N. Stefanou (Physical Review B, 2016)
Collective hybridized plasmon modes, which enable strong magnetooptical coupling and consequent enhanced Faraday effect in three-dimensional periodic assemblies of magnetic dielectric nanoparticles coated with a noble-metal shell, are studied by means of rigorous full electrodynamic calculations using an extension of the layer-multiple-scattering method, in conjunction with the effective-medium approximation. A thorough analysis of relevant photonic dispersion diagrams and transmission spectra provides a consistent explanation of the underlying physical mechanisms to a degree that goes beyond existing interpretation. It is shown that properly designed structures of such composite magnetoplasmonic nanoparticles offer a versatile platform for engineering increased and broadband Faraday rotation.